Sitagliptin and Fractures in Type 2 Diabetes: A Nationwide Population-Based Propensity-Matching Study - Lin, Shih-Yi; Hsu, Wu-Huei; Lin, Cheng-Chieh; Lin, Cheng-Li; Tsai, Chun-Hao; Yeh, Hung-Chieh; Hsu, Chung-Y.; Kao, Chia-Hung (Frontiers in Pharmacology, 2018)
Background: Sitagliptin, a dipeptidyl peptidase-4 inhibitor possibly affects bone turnover. We conducted this cohort study to determine whether sitagliptin is associated with an increased risk of fracture. Methods: The sitagliptin cohort included 1578 patients aged 20 years and above. The nonsitagliptin cohort comprised propensity-score matched patients at a ratio of 1:1. The primary outcome was the incidence of fractures, which was evaluated using Kaplan–Meier survival analysis and proportional hazards modeling. Results: The mean age of patients in the sitagliptin and nonsitagliptin cohorts was 63.1 and 63.3 years, respectively. The incidence of fractures in the sitagliptin cohort was 46 per 1000 person-years and that in the nonsitagliptin cohort was 40.8 per 1000 person-years. Compared with patients in the nonsitagliptin cohort, those in the sitagliptin cohort who received sitagliptin for ≥ 250 days had a higher risk of fracture (aHR = 1.32, 95% CI = 1.06–1.64). Conclusion: Using sitaglipin ≥ 250 days was associated with an increased risk of fracture.